Medicines information provided by pharmaceutical representatives: a comparative study in Australia and Malaysia - Othman, Noordin; Vitry, Agnes I.; Roughead, Elizabeth E; Ismail, Shaiful B; Omar, Khairani (BioMed Central, 2010)
Background: